Inhibitory of active dual cancer targeting 5-Fluorouracil nanoparticles on liver cancer in vitro and in vivo - Cheng, Mingrong; Dai, Dejian (Frontiers in Oncology, 2022)
The chitosan (CS) material as the skeleton nano-drug delivery system has the advantages of sustained release, biodegradability, and modifiability, and has broad application prospects. In the previous experiments, biotin (Bio) was grafted onto CS to synthesize biotin-modified chitosan (Bio-CS), and it was confirmed that it has liver cancer targeting properties. Single-targeted nanomaterials are susceptible to pathological and physiological factors, resulting in a state of ineffective binding between ligands and receptors, so there is still room for improvement in the targeting of liver cancer. Based on the high expression of folate (FA) receptors on the surface of liver cancers, FA was grafted onto Bio-CS by chemical synthesis to optimize the synthesis of folic acid-modified biotinylated chitosan (FA-CS-Bio), verified by infrared spectroscopy and hydrogen-1 nuclear magnetic resonance spectroscopy. The release of FA-CS-Bio/fluorouracil (5-FU) had three obvious stages: fast release stage, steady release stage, and slow release stage, with an obvious sustained release effect. Compared with Bio-CS, FA-CS-Bio could promote the inhibition of the proliferation and migration of liver cancer by 5-FU, and the concentration of 5-FU in hepatoma cells was significantly increased dose-dependently. Laser confocal experiments confirmed that FA-CS-Bio caused a significant increase in the fluorescence intensity in liver cancer cells. In terms of animal experiments, FA-CS-Bio increased the concentration of 5-FU in liver cancer tissue by 1.6 times on the basis of Bio-CS and the number of monophotons in liver cancer tissue by in vivo dynamic imaging experiments was significantly stronger than that of Bio-CS, indicating that the targeting ability of FA-CS-Bio was further improved. Compared with Bio-CS, FA-CS-Bio can significantly prolong the survival time of 5-FU in the orthotopic liver cancer transplantation model in mice, and has a relieving effect on liver function damage and bone marrow suppression caused by 5-FU. In conclusion, FA-CS-Bio nanomaterials have been optimized for synthesis. In vivo and in vitro experiments confirmed that FA-CS-Bio can significantly improve the targeting of liver cancer compared with Bio-CS. FA-CS-Bio/5-FU nanoparticles can improve the targeted inhibition of the proliferation and migration of liver cancer cells, prolong the survival period of tumor-bearing mice, and alleviate the toxic and side effects.